Depressive symptoms, HIV-related stigma and ART adherence among caregivers of children in vulnerable households in rural southern Malawi - Spielman, Kathryn L. (PLoS One, 2021)
BACKGROUND: Few studies have explored the association between depressive symptoms, HIV infection and stigma in vulnerable populations. The objective of this study is to examine factors associated with depressive symptoms among caregivers living in vulnerable households in Malawi and assess how reported depressive symptoms and other factors affect ART adherence among caregivers who report testing positive for HIV and currently on ART. METHODS: We interviewed 818 adult caregivers of children aged 0–17 years living in vulnerable households in 24 health facility catchment areas in five districts in rural southern Malawi in 2016–2017. Vulnerable households had either economic and food insecurity, or chronic illness. Questions on five depressive symptoms were used. ART adherence was self-report of not forgetting to take ART medication in the last week. Perceived and anticipated measures of stigma were used. Multivariable linear and logistic regressions documented relationships between depressive symptoms, self-reported HIV status, HIV-related stigma, and ART adherence. RESULTS: Most caregivers were women (86.2%); about one third had no spouse or live-in partner. Fifty-seven percent of caregivers reported having three or more depressive symptoms. Forty-one percent of caregivers reported testing positive for HIV. Self-reported HIV positive status was associated with depressive symptoms (adjusted coeff = 0.355, p-value <0.001), which were in turn associated with poorer ART adherence among caregivers (aOR 0.639, p-value = 0.023). HIV-related stigma was also associated with depressive symptoms for caregivers who reported having HIV (coeff = 0.302, p-value = 0.028) and those who reported testing negative for HIV (coeff = 0.187, p-value <0.001). Having social support was associated with lower depressive symptoms (coeff = -0.115, p = 0.007). HIV-related stigma, having social support, and other socio-demographic characteristics were not found to be associated with ART adherence. CONCLUSIONS: Addressing mental health among caregivers in vulnerable households may be an important step toward achieving viral suppression among vulnerable populations living with HIV in Malawi. Integrating depression screening into HIV care and treatment protocols could be a promising intervention to improve longer-term outcomes.